2015
DOI: 10.1111/raq.12131
|View full text |Cite
|
Sign up to set email alerts
|

Lymphocystis disease virus: its importance in aquaculture

Abstract: Lymphocystis disease virus (LCDV) is the causative agent of a well-known fish viral disease that is characterized by hypertrophy of fibroblastic cells in the connective tissue. This viral disease affects more than 125 wild and cultured species of teleost fish from marine and freshwater environments and has a cosmopolitan geographical distribution. In aquaculture systems, the prevalence of LCDV infection is very high, likely reflecting the horizontal transmission of this virus. The incidence rate of the disease… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
37
0
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(46 citation statements)
references
References 156 publications
(315 reference statements)
0
37
0
5
Order By: Relevance
“…Our study is focused on LCDV as there are no cost-effective treatments against viral infections (e.g., Assefa and Abunna 2018). Lymphocystis is an iridovirus (DNA virus) broadly documented to occur in many freshwater and marine fish around the world in both wild and farmed fish (e.g., Sahoo and Goodwin 2012;Yanong 2013;Borrego et al 2017). Typical signs of lymphocystis-infected fish are mostly external nodular, wart-like growths on the fins, skin, or gills that can advance from chronic to systemic infections (Yanong 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Our study is focused on LCDV as there are no cost-effective treatments against viral infections (e.g., Assefa and Abunna 2018). Lymphocystis is an iridovirus (DNA virus) broadly documented to occur in many freshwater and marine fish around the world in both wild and farmed fish (e.g., Sahoo and Goodwin 2012;Yanong 2013;Borrego et al 2017). Typical signs of lymphocystis-infected fish are mostly external nodular, wart-like growths on the fins, skin, or gills that can advance from chronic to systemic infections (Yanong 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Members of the genus Lymphocystivirus , family Iridoviridae, are the causative agents of the lymphocystis disease (LCD), a pathology that affects more than 150 fish species from both marine and freshwater environments (Borrego et al ). To date, three species have been recognized in the genus, Lymphocystis disease virus 1 (LCDV1) isolated from European flounder ( Platichthys flesus ), Lymphocystis disease virus 2 (LCDV‐C) isolated from Japanese flounder ( Paralichthys olivaceus ) and Lymphocystis disease virus 3 (LCDV‐Sa) isolated from gilthead seabream ( Sparus aurata ) (Chinchar et al ).…”
Section: Introductionmentioning
confidence: 99%
“…The lymphocystis disease (LCD) is a highly contagious viral infection responsible for high economic losses in the aquaculture industry worldwide [1]. The causative agent is the lymphocystis disease virus (LCDV) that belongs to the genus Lymphocystivirus, family Iridoviridae.…”
Section: Introductionmentioning
confidence: 99%
“…Then, the virus actively multiplies in host cells giving rise to the typical lesions (named lymphocysts) consisting of irregularly shaped, randomly distributed white masses in the integumentary surfaces that in severe infections aggregate in nodular structures [2]. Experimental challenges have demonstrated that at least three weeks after LCDV injection are required for the observation of clinical signs [1,3,4]. Once the lesions appear, the disease spans for approximately 20 days, the time required for the hypertrophic dermal cells to mature and break resulting in high morbidity but low mortality rates unless secondary infections occur [2,3,5,6].…”
Section: Introductionmentioning
confidence: 99%